Value of Antibody Determinations in Chronic Dysimmune Neuropathies - Stefano Tozza; Emanuele Spina; Aniello Iovino; Rosa Iodice; Raffaele Dubbioso; Lucia Ruggiero; Maria Nolano; Fiore Manganelli (Brain Sciences, 2022)
Chronic dysimmune neuropathies encompass a group of neuropathies that share immune-mediated pathomechanism. Chronic dysimmune antibody-related neuropathies include anti-MAG neuropathy, multifocal motor neuropathy, and neuropathies related to immune attack against paranodal antigens. Such neuropathies exhibit distinguishing pathomechanism, clinical and response to therapy features with respect to chronic inflammatory demyelinating polyradiculoneuropathy and its variants, which represent the most frequent form of chronic dysimmune neuropathy. This narrative review provides an overview of pathomechanism; clinical, electrophysiological, and biochemical features; and treatment response of the antibody-mediated neuropathies, aiming to establish when and why to look for antibodies in chronic dysimmune neuropathies.